APPETITE REGULATION IN RELATION TO ENERGY PROVISION - Fatima, Sadia; Ahmed, Nasir; Fatima, Fozia; Wazir, Salim (Journal of Ayub Medical College Abbottabad, 2016)
Background: Appetite control is a very complex process which influences the short term feeding behaviour and a long term adaptive process that responds to the energy input. Appetite control and food intake is influenced by a combination of behavioural, psychological and neuro-endocrine influences. Methods: For identification of articles search engines of the databases EMBASE, OVID, Pub med and MEDLINE were used for papers published from 2002 to 2015 in English language. Results: The higher endogenous peptide YY (PYY) and cholecystokinin (CCK) and lower ghrelin levels are not always associated with subjective feelings of fullness or hunger and a decreased energy intake which highlights the fact that appetite control and food intake is a very intricate process. Conclusion: When food is ingested, numerous physiological, hormonal, social and psychological processes are triggered in an intricate manner. Therefore, it can be said that ghrelin, PYY and CCK are just few pieces, which contributes to the process of appetite control and energy intake. Keywords: Appetite, appetite hormones, ghrelin, CCK, PYY, control of energy intake